A retrospective analysis on flap design used in mandibular carcinoma - a hospital-based study - HARINI.G; SELVARASU, KATHIRAVAN; DR. BALAKRISHNA R N (The journal of contemporary issues in business and government, 2020)
The squamous cell carcinoma is by far the most commonly found tumour of the oral cavity. This includes the tongue, floor of mouth, retromolar trigone, and lips. The mainstay of treatment for these patients in the surgical resection, neck dissection,radiation,and local nodal basins in the neck. The aim of the study is to investigate the flap design used in Mandibular carcinoma among the patients who visited the Department of oncology between june 1 st 2019- 1st april 2020. Data was extracted by reviewing patient records. Out of 57 patients 22 patients were diagnosed with mandibular carcinoma. There was male predominance with 90.91% followed by females with 9.09%. The age group of 51-60 (50%) followed by 41-50 years (36.36%) was affected by mandibular carcinoma. Buccal carcinoma (77.27%) was the most commonly affected site. Cheek splitting was the most common flap used to excise the carcinoma. (63.64%) followed by lingual- releasing flap(16.16%), lip-splitting flap(9.09%) and visor flap(9.09%). Regarding the site of carcinoma and type of approach used, cheek splitting approach was used predominantly for buccal carcinoma lesions; lingual releasing approach was used to operate retromolar trigone carcinomas; Lip-splitting approach and visor flap approach were used for tongue carcinomas .The association between the design of flap used and site of occurrence of lesion was found to be statistically significant (p value- 0.02).